Emergence of cooperation in congested road networks using ICT and future and emerging technologies: A game-based review. (November 2016) - Klein, Ido; Ben-Elia, Eran
Highlights: Managing traffic congestion by enhancing cooperation in road networks using ICT. Cooperation is an emergent social state related to the dynamics and complexity of road traffic. Game theory and behavioral economics show that cooperation can be leveraged to solve traffic congestion. We review applications in route, mode and departure time choice problems. We discuss the methodological opportunities in serious games and game-based models. Abstract: Information and communications technologies (ICT) and future and emerging technologies (FET) are expected to revolutionize transportation in the next generation. Travelers' behavioral adaptation is a key to their success. We discuss the notion of managing traffic congestion by enhancing cooperation in road networks enabled with ICT and FET. Cooperation is an emergent social state related to the dynamics and complexity of road traffic and reinforced learning. Game theory and research in behavioral economics show that cooperation can be leveraged to efficiently solve social dilemmas similar to traffic congestion. We review the applicability of behavioral economics and game theory concepts to route, mode and departure time choice problems. Beyond advancing theory, research on cooperation in the context of transportation is still in its infancy. We discuss state-of-the-art methodologies and their weaknesses and review the unexplored opportunities inherent in game-based methodologies. A behavioral-technological research agenda for FET is also discussed.